Smart free-standing film force-assembled by Ti3C2Tx/CNC with high sensitivity to humidity and near-infrared light. (8th May 2023) - Meng, Xiangqi; Lian, Zhong; Chang, Fan; Cheng, Haoge; Zhang, Jingyue; Ouyang, Xiao; Zhang, Xinyue; Ma, Ning; Wei, Hao
Graphical abstract: Highlights: The hydrophilic Ti3 C2 Tx /CNC film with the directional aligned structure can directionally actuate under the humidity. The excellent photothermal conversion ability of the hybrid film can respond to the NIR light fast in short time. By depositing thermochromism materials, the Ti3 C2 Tx /CNC hybrid film can realize the visual temperature detection. Abstract: Smart films that can specifically recognize the outer surrounding change and make rapid motion behavior, have presented their potential application in composing intelligent actuators. Herein, we have prepared a hydrophilic free-standing film with the nacre-like layered and directional aligned structure by vacuum-filtering the mixed suspension of Ti3 C2 Tx nanosheets and cellulose nanocrystal (CNC). Because of the axial Young's modulus from the oriented arrangement of CNC and Ti3 C2 Tx, the assembled hybrid film can achieve fast and directed humidity-driven performance, and obtain a specific bending angle by controlling the asymmetric humidity value. Besides, the introduction of CNC also increased the surficial roughness of the hybrid film compared to the pure Ti3 C2 Tx film, which lengthened the light propagation path. Based on the good photothermal conversion ability of Ti3 C2 Tx nanosheets around the NIR region, the hybrid film presented ultra-high NIR conversing efficiency that can rapidly heat up to 178.2 °C only under the NIR (808 nm) power of 0.45 W/cm 2 . Therefore, by depositing thermochromism materials with different color change points, the composited film can realize visual temperature detection. This TC/CNC film with the ability of humidity and NIR sensing will satisfy the further demand for designing smart equipment.